The Effect Of Product Quality And Promotion On Purchase Decision - Ristanti, Vivi; Haryati, Tety; Igo, Arif (Jurnal Ilmiah Manajemen Kesatuan, 2024)
This study aims to determine: 1. The effect of product quality on purchasing decisions for Oppo smartphones for STIM Budi Bakti students; 2. The influence of promotions on purchasing decisions for Oppo smartphones for STIM Budi Bakti students; 3. The influence of product quality and promotion together on purchasing decisions for Oppo smartphones for STIM Budi Bakti students. This type of research is quantitative research. The sample in this study were STIM Budi Bakti students. The sample in this study was part of STIM Budi Bakti students, totaling 90 respondents. Data collection techniques in this study using a questionnaire. Data analysis techniques using Simple Linear Regression and Multiple Linear Regression. The results of research on Product Quality on Purchasing Decisions are known to have an influence of 60,7%. whereas for the results of Promotional research on Purchasing Decisions it is known to have an influence of 57,9%. The results of research on product quality and promotion on purchasing decisions are known to have an influence of 62,6%. From this study, it shows that there is an influence of product quality and promotion on consumer satisfaction of Oppo smartphones for STIM Budi Bakti students. Keywords: Product quality, Promotion, Purchasing decisions